Audit fiasco: Serba Dinamik ‘serba tak kena’ - Zainal Abidin, Nor Hafizah; Mohd Alwi, Norhayati; Mokhtar, Norsyahida (IIUM Press, 2023)
Serba Dinamik has been listed a couple of years ago and achieved tremendous growth in financial performance. The business expansion across different regions around the world has boosted the market value of the company. However, in the financial year audit ended 2020, several audit issues highlighted by the auditor have created a wave in the industry on the issue of audit failure or corporate failure. The case outlined events that happened throughout the turbulence and discussed the roles and responsibilities of auditor in handling the situation.